1989
DOI: 10.1021/bi00432a017
|View full text |Cite
|
Sign up to set email alerts
|

Formylglycinamide ribonucleotide synthetase from Escherichia coli: cloning, sequencing, overproduction, isolation, and characterization

Abstract: The purL gene of Escherichia coli encoding the enzyme formylglycinamidine ribonucleotide (FGAM) synthetase which catalyzes the conversion of formylglycinamide ribonucleotide (FGAR), glutamine, and MgATP to FGAM, glutamate, ADP, and Pi has been cloned and sequenced. The mature protein, as deduced by the structural gene sequence, contains 1628 amino acids and has a calculated Mr of 141,418. Comparison of the purL control region to other pur loci control regions reveals a common region of dyad symmetry which may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
84
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(88 citation statements)
references
References 57 publications
3
84
0
Order By: Relevance
“…All three were initially identified as purR mutations by their P1 linkage to the man and pdxH loci and confirmed by complementation with purR+ plasmid pPR1002 (25 (18,24), purMN (28), purL (26), purEK (30,36), purHD (1), purC (Tiedeman et (Fig. 2).…”
Section: Resultsmentioning
confidence: 96%
“…All three were initially identified as purR mutations by their P1 linkage to the man and pdxH loci and confirmed by complementation with purR+ plasmid pPR1002 (25 (18,24), purMN (28), purL (26), purEK (30,36), purHD (1), purC (Tiedeman et (Fig. 2).…”
Section: Resultsmentioning
confidence: 96%
“…They demonstrated that a specific sequence (ACGCAAACGTTTTCTT) in the purF operator DNA was protected from DNaseI digestion by crude cell extracts of purR+ cells, but not of purR-cells. Sequences similar to the protected region (PUR box) in purF are present in the regulatory regions of purMN [4], purL [5] and purEK [3,61 of E. coli. It has been suggested that the expression of these genes is co-regulated with purF in both E. coli and Scilmonclla typhimurium [7], and also that hypoxhanthine and guanine are the corepressors in S. typhimurium [8].…”
mentioning
confidence: 99%
“…2 Gn-ATs are classified primarily into two subfamilies, classes I and II, according to their glutaminase domains. 3 Glutaminase domains of class I Gn-ATs consist of B200 amino-acid residues and have a cysteine protease-type catalytic triad, formed by Cys, His, and Gln. In contrast, class II Gn-ATs have a glutaminase domain in which the N-terminal Cys is the only catalytic residue.…”
Section: Introductionmentioning
confidence: 99%